1999
DOI: 10.1523/jneurosci.19-04-01517.1999
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 Mediates a Rapid Inflammatory Response After Injection of Adenoviral Vectors into the Brain

Abstract: Adenovirus-mediated gene transfer into the brain is associated with significant inflammation and activation of anti-vector and anti-transgene immune responses that curtail the gene delivery of adenoviruses and therapeutic efficacy. Elucidating the molecular mediators of inflammatory and immune responses to adenoviruses injected into the brain should allow us to inhibit their inflammatory actions, thereby reducing vector clearance and enhance adenoviral-mediated gene transfer into the CNS. Cytokines are primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 102 publications
(51 citation statements)
references
References 39 publications
0
51
0
Order By: Relevance
“…Moreover, the fever response upon injection of adenoviral vectors into the lateral ventricle is blocked by antagonists of IL-1, demonstrating that the fever response is induced by IL-1, rather than TNFa. 20 Similar increases in IL-6 and TNFa are detected upon systemic injections of adenoviral vectors. 22,23 Also, the fever response elicited was independent of the transgene encoded by the adenoviral vectors, but did depend on the integrity of the viral capsid.…”
Section: Brain Inflammation Upon Injection Of Viral Vectorsmentioning
confidence: 85%
See 2 more Smart Citations
“…Moreover, the fever response upon injection of adenoviral vectors into the lateral ventricle is blocked by antagonists of IL-1, demonstrating that the fever response is induced by IL-1, rather than TNFa. 20 Similar increases in IL-6 and TNFa are detected upon systemic injections of adenoviral vectors. 22,23 Also, the fever response elicited was independent of the transgene encoded by the adenoviral vectors, but did depend on the integrity of the viral capsid.…”
Section: Brain Inflammation Upon Injection Of Viral Vectorsmentioning
confidence: 85%
“…[17][18][19] Cytokine 20 and cellular 21 inflammatory reactions are elicited upon injection of first-generation adenoviral vectors. This is reflected in a release of the cytokines IL-1, IL-6, TNFa, and the stimulation of a fever response, 20 when adenovirus is injected into the third ventricle. Cytokine levels increase very rapidly, with a peak observed at 1.5 h after virus injection, and a time course similar to the fever response, returning to normal within 24 h. Injection of adenovirus into the striatum elicits an increase of IL-1 and IL-6, but not TNFa or fever.…”
Section: Brain Inflammation Upon Injection Of Viral Vectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Cartmell et al 10 showed that IL-1 is an important mediator of the innate early immune response to adenovirus in the brain. In rats, IL-1 synthesis (and not TNF-␣), was associated with the rise in body temperature observed within a few hours following intraventricular recombinant adenovirus administration.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies showed a role of TNF-␣, IL-1 and IL-6 in initiating an aspecific early immune response. 9,10 In vitro studies also suggest a critical role of adenovirus-induced IL-8 production in eliciting an innate immune response against the vector. 11,12 In two nonhuman primates, cytokine production (IL-8 and IL-1, IL-2, IL-6, TNF-␣ and IFN-␥) in the CSF was determined 24, 48 and 72 h after intrathecal adenolacZ injection.…”
Section: Introductionmentioning
confidence: 99%